2002
DOI: 10.1097/00007632-200210150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA and Protein Levels of Proteoglycans of the Anulus Fibrosus and Nucleus Pulposus During Intervertebral Disc Degeneration

Abstract: Cells of the anulus fibrosus and nucleus pulposus react to tissue degeneration differently. Decreased mRNA expression by nucleus pulposus cells and declining protein content of the matrix make the nucleus more vulnerable to degeneration than the anulus. The cells in the anulus fibrosus respond to early degeneration by upregulating biosynthetic processes. However, in heavily degenerated tissues, the decline in the synthesis of aggrecan and the increase in the concentrations of small proteoglycans may be respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
145
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 27 publications
9
145
0
Order By: Relevance
“…These observations were in accordance with previous reports (Schmid et al, 1991;Feng and Song, 2004;Gruber et al, 2002). As reported previously, loss of water and glycosaminoglycans suggested degeneration of the nucleus pulposus (Cs-Szabo et al, 2002). In our results, the fibrosis of the nucleus pulposus, or intervertebral disc herniation was not observed in the rats of the aged group, which may be due to the discs of rats enduring less pressure than humans since they were reptiles.…”
Section: Discussionsupporting
confidence: 93%
“…These observations were in accordance with previous reports (Schmid et al, 1991;Feng and Song, 2004;Gruber et al, 2002). As reported previously, loss of water and glycosaminoglycans suggested degeneration of the nucleus pulposus (Cs-Szabo et al, 2002). In our results, the fibrosis of the nucleus pulposus, or intervertebral disc herniation was not observed in the rats of the aged group, which may be due to the discs of rats enduring less pressure than humans since they were reptiles.…”
Section: Discussionsupporting
confidence: 93%
“…There is some evidence that fragments may be more potent in cell signalling than intact molecules [27]. The presence of SLRPs within the IVD has been welldocumented [1,6,12,14,18,30], although as far as we are aware this is the first report of keratocan in human IVD. Whilst during aging and degeneration, the distribution of SLRPs within the disc extracellular matrix has been shown to vary, little has been reported on fragmentation, especially in pathological human discs.…”
Section: Discussionmentioning
confidence: 82%
“…An increase of collagen type I is commonly encountered in degenerating discs in vivo. [47][48][49][50][51] Using immunohistochemistry, Le Maitre et al 52 demonstrated the same pattern of collagen types in an unconstrained culture of human discs. Two independent investigations on rabbit disc stab models also demonstrated a degenerative matrix gene expression in the postinterventional course.…”
Section: Discussionmentioning
confidence: 91%